A rapid method for the screening of fatty acids in lipids in plasma or serum without prior extraction. (March 2022) - Liu, Ge; Makrides, Maria; Coates, Penelope; Lam, Khoa; Ranieri, Enzo; Mas, Emilie; Gibson, Robert A
Highlights: We have developed a one-step in situ method that bypasses the need to extract the lipids from plasma/serum, thus saving time and materials. Our new method yields both compositional and quantitative analysis of the fatty acids of serum identical to conventional standard methods. Our new method is ideal for screening of clinical biomarkers such as n-3 LCPUFA status involving very large numbers of samples. Abstract: Serum or plasma are the commonly used blood fractions to determine the relationship between dietary and circulating fatty acids in health and disease. Most methods available for the measurement of fatty acids in serum or plasma (referred to as serum henceforth) require prior extraction with organic solvents. We have determined that it is possible to directly convert the lipids in aqueous biological samples to fatty acid methyl esters (FAME) without prior extraction, providing that the ratio of serum to transmethylation solvent does not exceed 10%. Our in-vial transmethylation system uses 50uL serum pipetted into 2 mL screw top GC vials containing 1 mL of 1% H2 SO4 in methanol at 50 °C and subsequent FAME extracted in the same vial into 300uL heptane. The system yields both compositional and quantitative analysis of the fatty acids of serum identical to conventional standard methods. Evaluation of our new serum assay confirms significant correlations between the fatty acid measures and those obtained from conventional standard assay for all fatty acids ( r > 0.99, P <0.0001), including the n-6 ( r  = 0.998, P <0.0001) and n-3 long chain polyunsaturated fatty acids ( r  = 0.993, P <0.0001). There were high levels of agreement between methods on Bland -Altman analysis, indicating the interchangeability of the methods. These results establish our new method as reliable for the assessment of fatty acid composition of small volumes of serum useful for high throughput situations that limits the volume of organic solvents and technical input.